International Conference on Malaysia History 2004, 23-25 Aug. 2004, Kuala Lumpur - International Conference on Malaysian History 2004 (2004 : University of Malaya, Kuala Lumpur) (Kuala Lumpur : University of Malaya, 2004)
33